Development of a Symptom Self-Management Guide for Older Chinese Americans Kidney Receiving Replacement Therapy - Carolyn Sun; Wing Cheung; Kathryn Corpuz; Jingjing Shang; Patricia W. Stone (Hindawi Limited, 2024)
Aim. To assess the acceptability of a symptom self-management booklet among older Chinese Americans receiving kidney replacement therapy. Background. In previous work, we identified commonly occurring, bothersome symptoms and strategies used in this population to ameliorate symptoms. We used these data to develop a symptom self-management booklet in English, traditional, and simplified Chinese. Introduction. In the United States, the prevalence of kidney disease is 1.5 times higher in Asians compared to whites. With the many symptoms associated with this disease, self-management of symptoms would be particularly helpful. Methods. Seven older Chinese Americans receiving kidney replacement therapy and their caregivers were interviewed to assess the acceptability of the booklets. We reviewed participant feedback on content, graphics, and design, reading experience, suggestions for improvement, and health information sources using the inductive thematic method. Results. Overall, patients confirmed acceptability of these self-management booklets across all domains. Discussion. This study validated the booklet as a source of health information for older Chinese American patients with kidney disease, which some studies suggest are preferred to electronic materials or methods in this population. Health care providers can use the resultant booklets when caring for these patients to provide culturally sensitive information on self-management of symptoms. Conclusion and Implications for Nursing. These booklets provide a free resource tailored to an underserved population and may help nurses and nurse practitioners provide care with cultural humility. Implications for Health Policy. Embracing community-based participatory research, as was done in this study, can help create culturally appropriate patient education materials that empower patient symptom self-management and promote informative and culturally sensitive conversations between patients, families, and providers.